Peritumoral Brain Edema after Stereotactic Radiosurgery for Asymptomatic Intracranial Meningiomas: Risks and Pattern of Evolution - Hoe, Yeon (J Korean Neurosurg Soc, 2015)
OBJECTIVE: To investigate the risks and pattern of evolution of peritumoral brain edema (PTE) after stereotactic radiosurgery (SRS) for asymptomatic intracranial meningiomas. METHODS: A retrospective study was conducted on 320 patients (median age 56 years, range 24-87 years) who underwent primary Gamma Knife radiosurgery for asymptomatic meningiomas between 1998 and 2012. The median tumor volume was 2.7 cc (range 0.2-10.5 cc) and the median follow-up was 48 months (range 24-168 months). Volumetric data sets for tumors and PTE on serial MRIs were analyzed. The edema index (EI) was defined as the ratio of the volume of PTE including tumor to the tumor volume, and the relative edema indices (rEIs) were calculated from serial EIs normalized against the baseline EI. Risk factors for PTE were analyzed using logistic regression. RESULTS: Newly developed or increased PTE was noted in 49 patients (15.3%), among whom it was symptomatic in 28 patients (8.8%). Tumor volume larger than 4.2 cc (p<0.001), hemispheric tumor location (p=0.005), and pre-treatment PTE (p<0.001) were associated with an increased risk of PTE. rEI reached its maximum value at 11 months after SRS and decreased thereafter, and symptoms resolved within 24 months in most patients (85.7%). CONCLUSION: Caution should be exercised in decision-making on SRS for asymptomatic meningiomas of large volume (>4.2 cc), of hemispheric location, or with pre-treatment PTE. PTE usually develops within months, reaches its maximum degree until a year, and resolves within 2 years after SRS.